Characterization of Atrial and Ventricular Structural Remodeling in a Porcine Model of Atrial Fibrillation Induced by Atrial Tachypacing - Citerni, Carlotta; Kirchhoff, Jeppe; Olsen, Lisbeth Høier; Sattler, Stefan Michael; Gentilini, Fabio; Forni, Monica; Zannoni, Augusta; Grunnet, Morten; Edvardsson, Nils; Bentzen, Bo Hjorth; Diness, Jonas Goldin (Frontiers in Veterinary Science, 2020)
Background: Atrial fibrillation (AF) is characterized by electrical and structural remodeling. Irregular and/or fast atrio-ventricular (AV) conduction during AF can result in AV dyssynchrony, tachymyopathy, pressure and volume overload with subsequent dilatation, valve regurgitation, and ventricular dysfunction with progression to heart failure. Objective: To gain further insight into the myocardial pathophysiological changes induced by right atrial tachypacing (A-TP) in a large animal model. Methods: A total of 28 Landrace pigs were randomized as 14 into AF-induced A-TP group and 14 pigs to control group. AF pigs were tachypaced for 43 ± 4 days until in sustained AF. Functional remodeling was investigated by echocardiography (after cardioversion to sinus rhythm). Structural remodeling was quantified by histological preparations with picrosirius red and immunohistochemical stainings. Results: A-TP resulted in decreased left ventricular ejection fraction (LVEF) accompanied by increased end-diastolic and end-systolic left atrium (LA) volume and area. In addition, A-TP was associated with mitral valve (MV) regurgitation, diastolic dysfunction and increased atrial and ventricular fibrotic extracellular matrix (ECM). Conclusions: A-TP induced AF with concomitant LV systolic and diastolic dysfunction, increased LA volume and area, and atrial and ventricular fibrosis.